Validation of albumin, bilirubin, and platelet criteria for avoiding screening endoscopy in patients with advanced fibrosis. Issue 8 (13th July 2020) - Tamaki, Nobuharu; Kurosaki, Masayuki; Higuchi, Mayu; Kirino, Sakura; Inada, Kento; Yamashita, Koji; Sekiguchi, Shuhei; Hayakawa, Yuka; Osawa, Leona; Takaura, Kenta; Maeyashiki, Chiaki; Kaneko, Shun; et al.
Abstract : Aim: The albumin, bilirubin, and platelet (ABP) criteria was proposed to avoid screening endoscopy for detecting high‐risk varices (HRV) and it has high diagnostic accuracy. We carried out a retrospective cross‐sectional study to verify the diagnostic accuracy. Methods: A total of 610 patients with advanced fibrosis were enrolled in the study. ABP criteria are defined as follows: albumin >4.0 g/dL, bilirubin <22 μmol/L, and platelets >114 000/μL. Results: Background liver disease were hepatitis C/hepatitis B/non‐alcoholic fatty liver disease/others:405 (66.4%)/67 (10.5%)/78 (12.8%)/60 (10.3%). A total of 105 patients (17.2%) had HRV. In multivariate analysis, serum bilirubin <22 μmol/L (HR 2.00, 95% CI 1.2–3.4), albumin >4.0 g/dL (HR 2.56, 95% CI 1.7–3.8), and platelets >114 000/μL (HR 3.52, 95% CI 2.1–5.8) levels were independently associated with no presence of HRV. When the ABP criteria were examined, 200 patients (32.8%) fulfilled the criteria, and 194 patients had no HRV (positive predictive value 97.0%) When classified by etiologies (hepatitis C/hepatitis B/non‐alcoholic fatty liver disease), positive predictive value were 97.7/100/92.0%, respectively. Conclusions: The ABP criteria are easy to examine, because they use only standard laboratory tests, and they are available for screening patients who might avoid endoscopy regardless of etiologies.